Let's work an example like yours that will require similar steps to complete.
Say we need to solve the following equation for 'b':
(5-b) + 4(3b - 1) = 23.
The first step would be to expand the LHS by distributing the 4.
5 - b + 12b - 4 = 23.
Now simplify this as follows, remembering we can reorder the terms if it helps to make it more clear.
12b - b + 5 - 4 = 23
11b + 1 = 23.
Subtract 1 from both sides to begin isolating 'b'.
11b = 22.
Finally, divide both sides by 11.
b = 2.
You would do well to check that this indeed is a correct solution to the original equation.
If you followed that example, I would suggest you try your problem again, as it is very similar to this example.
Hope that helps.